Strategic Agility and Trust-Based Consulting Architectures for Small and Medium-Sized Enterprises in Volatile Markets - Dr. Julian S. Everhart (Next Scientists International Journal JSSHRF, 2026)
Small and medium-sized enterprises (SMEs) operate under conditions of persistent volatility, resource scarcity, and institutional asymmetry that expose them to strategic fragility while simultaneously demanding rapid adaptive responses. In this context, business consulting has increasingly evolved from episodic advisory engagement to a structurally embedded capability for enabling organizational agility, leadership alignment, and sustainable performance. This article develops a comprehensive, theory-driven and practice-oriented research framework that integrates strategic agility, social exchange theory, leadership trust, and top management team (TMT) dynamics into a complex model of SME consulting. Anchored in the recent monographic work on a complex model of business consulting for SMEs (Kovalchuk, 2025), the study advances an interpretive, multi-level methodological design that synthesizes organizational theory, strategic management, and consulting science to explain how consulting interventions shape SME resilience and competitive renewal. The article addresses a critical gap in the literature by moving beyond linear, tool-based consulting paradigms toward a systems-based architecture in which consulting is understood as a dynamic capability co-produced by consultants and client organizations. Drawing on the integrative review of organizational agility (Bangura & Lourens, 2024), classical foundations of social exchange and power (Blau, 2017; Cropanzano & Mitchell, 2005), leadership trust (Dirks & Ferrin, 2002; Burke et al., 2007), and strategic agility (Doz & Kosonen, 2008, 2010), this research conceptualizes consulting as a governance mechanism that aligns strategic intent, organizational routines, and stakeholder expectations.